2012
DOI: 10.1038/onc.2011.617
|View full text |Cite
|
Sign up to set email alerts
|

MKNK1 is a YB-1 target gene responsible for imparting trastuzumab resistance and can be blocked by RSK inhibition

Abstract: Trastuzumab (Herceptin) resistance is a major obstacle in the treatment of patients with HER2-positive breast cancers. We recently reported that the transcription factor Y-box binding protein-1 (YB-1) leads to acquisition of resistance to trastuzumab in a phosphorylationdependent manner that relies on p90 ribosomal S6 kinase (RSK). To explore how this may occur we compared YB-1 target genes between trastuzumab-sensitive cells (BT474) and those with acquired resistance (HR5 and HR6) using genome-wide chromatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 51 publications
(71 reference statements)
2
62
0
Order By: Relevance
“…Interestingly, the preferred target logo, derived from the analysis of ChIP-Seq experiments, is consistent with the RNA-binding features of YB-1, and indeed resembles Kozak sequences. 127 Thus, we offer an alternative explanation for the many reports of YB-1 binding in ChIP experiments, and indeed ChIP-Seq, in transformed cells: 126 YB-1 could be transitorily located in an area physically 'close' to promoters, or other important regulatory regions, where transcriptional initiation decisions are made, but loaded on partially synthesized primary RNAs ( Figure 5). One finding consistent with this interpretation is that chromatin association of YB-1 is apparently lost upon treatment with ribonucleases, which destroys pre-mRNAs.…”
Section: The -Apparent -Paradox Of Y/ccaat Nf-y and Yb-1 In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the preferred target logo, derived from the analysis of ChIP-Seq experiments, is consistent with the RNA-binding features of YB-1, and indeed resembles Kozak sequences. 127 Thus, we offer an alternative explanation for the many reports of YB-1 binding in ChIP experiments, and indeed ChIP-Seq, in transformed cells: 126 YB-1 could be transitorily located in an area physically 'close' to promoters, or other important regulatory regions, where transcriptional initiation decisions are made, but loaded on partially synthesized primary RNAs ( Figure 5). One finding consistent with this interpretation is that chromatin association of YB-1 is apparently lost upon treatment with ribonucleases, which destroys pre-mRNAs.…”
Section: The -Apparent -Paradox Of Y/ccaat Nf-y and Yb-1 In Cancermentioning
confidence: 99%
“…YB-1-regulated genes, as summarized by Eliseeva et al, 71 were analyzed for the presence of YB-1 peaks in the YB-1 ChIP-Seq data reported by Astanehe et al, 126 and for NF-Y peaks present in ENCODE data of K562, HeLa-S3 and GM12878 cells (Wang et al 60 and Fleming and Struhl, submitted for publication)…”
Section: The -Apparent -Paradox Of Y/ccaat Nf-y and Yb-1 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…These upstream kinases activate mouse MNK1 via phosphorylation on Thr 197/202 [21]. Recent work shows that MNK1 can also be phosphorylated by p90 ribosomal protein S6 kinase (p90 rsk ), in a mechanism that confers trastuzumab resistance in HER-2 positive breast cancers [38]. The MNKs associate with the C-terminus of eIF4G, a vital interaction that brings the kinase into close enough proximity to phosphorylate eIF4E on Ser209 [5,39].…”
Section: Mapk-interacting Kinasesmentioning
confidence: 99%
“…The oncogenic effect of eIF4E overexpression in mouse models of lymphoma (28) and prostate cancer (22) is strictly dependent on the phosphorylation status of eIF4E. Activation of MNK contributes to cell proliferation, transformation, and metastasis (25,26); growth and survival during cancer development (19, 29 -33); or serum deprivation (34,35) and also contributes to cancer chemoresistance (36,37) (also reviewed in Ref. 38).…”
mentioning
confidence: 99%